THE EFFECT OF THE GAME-BASED LEARNING MODEL ASSISTED BY CARD SORT ON STUDENTS’ ACTIVENESS AND LEARNING OUTCOMES IN THE COORDINATION SYSTEM TOPIC - Alfini; Suryawati, Evi; Darmadi (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
The low level of students’ activeness and learning outcomes are among the many problems found in biology learning. The complexity of biological material, particularly in the coordination system topic, and the use of less innovative learning models are the main factors contributing to these issues. This study aims to determine the effect of applying the game-based learning model assisted by card sort on students’ activeness and learning outcomes in the coordination system topic. This research employed a quasi-experimental method with a Nonequivalent Group Posttest Only Design. The study was conducted at SMAN 7 Pekanbaru. The research samples were class XI.2 (experimental class) and class XI.7 (control class). Data were collected through observation using observation sheets, tests using test sheets, and documentation using documentation guidelines. The results showed that: (1) the average activeness score of students in the experimental class was 63.56 (active), while the average activeness score of students in the control class was only 55.83 (fairly active); (2) the average learning outcome score of students in the experimental class was 84.23 (good), while that of the control class was only 77.26 (fairly good). The hypothesis test results indicated that: (1) there was a highly significant effect of applying the game-based learning model assisted by card sort on students’ learning activeness (sig. value 0.000 < 0.05); and (2) there was a highly significant effect of applying the game-based learning model assisted by card sort on students’ learning outcomes (sig. value 0.000 < 0.05). This study indicates that integrating educational games with card media can enhance students’ activeness and learning outcomes in biology learning, especially for complex topics such as the coordination system. This learning model can be implemented at other educational levels to improve students’ activeness and learning outcomes.